2021
DOI: 10.1177/09636897211033778
|View full text |Cite
|
Sign up to set email alerts
|

Preventive and Therapeutic Effects of a Novel JAK Inhibitor SHR0302 in Acute Graft-Versus-Host Disease

Abstract: Acute graft-versus-host disease (aGVHD) is one of the most common complications of allogeneic hematopoietic stem cell transplantation (allo-HSCT). Janus kinase (JAK) inhibitors are considered as reliable and promising agents for patients with aGVHD. The prophylactic and therapeutic effects of SHR0302, a novel JAK inhibitor, were evaluated in aGVHD mouse models. The overall survival (OS), progression-free survival (PFS), bodyweight of mice, GVHD scores were observed and recorded. The bone marrow and spleen samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Interestingly, baricitinib was superior to ruxolitnib in preventing GVHD-induced mortality. More recently, Sun and colleagues utilized a highly selective JAK1 inhibitor (SHR0302) (62) and demonstrated improved overall survival when compared to vehicle treated controls (63). SHR0302 also reduced the infiltration of immune cells into the GI tract through reduction of CXCR3 expression on donor T cells as well as mitigated the release of the proinflammatory cytokines, IL-6, IFN-g, and TNF-a.…”
Section: Janus Kinase Inhibitionmentioning
confidence: 99%
“…Interestingly, baricitinib was superior to ruxolitnib in preventing GVHD-induced mortality. More recently, Sun and colleagues utilized a highly selective JAK1 inhibitor (SHR0302) (62) and demonstrated improved overall survival when compared to vehicle treated controls (63). SHR0302 also reduced the infiltration of immune cells into the GI tract through reduction of CXCR3 expression on donor T cells as well as mitigated the release of the proinflammatory cytokines, IL-6, IFN-g, and TNF-a.…”
Section: Janus Kinase Inhibitionmentioning
confidence: 99%
“…Currently, SHR0302 is undergoing a phase III study (NCT04333771) of treatment for RA patients at once‐daily doses of 4 or 8 mg. In addition to the indication of RA mentioned in this article, SHR0302 is also being developed for the treatment of various other autoimmune inflammatory disorders 6–8 …”
Section: Introductionmentioning
confidence: 99%
“…In addition to the indication of RA mentioned in this article, SHR0302 is also being developed for the treatment of various other autoimmune inflammatory disorders. [6][7][8] In a phase I single ascending dose study, SHR0302 demonstrated a favourable safety profile at a dose range of 1-100 mg in healthy subjects. The plasma exposure of SHR0302 increased in an approximately dose-proportional manner across the evaluated dose range, indicating linear pharmacokinetic (PK) characteristics of the drug.…”
mentioning
confidence: 99%
“…SHR0302 is an oral and highly selective Janus kinase 1 (JAK1) inhibitor. JAK1 is an intracellular tyrosine kinase that controls many functions of innate and adaptive immunity by sending signals from extracellular cytokines (e.g., interleukin‐2 and ‐6 and interferons) and activating downstream cascades via the JAK–STAT pathway 1–3 . By inhibiting JAK1, SHR0302 has the potential to control autoimmune or immune‐mediated disorders, including rheumatoid arthritis (RA) 4 and atopic dermatitis (AD) 1 .…”
Section: Introductionmentioning
confidence: 99%